СОВЕРШЕНСТВОВАНИЕ МЕТОДОВ РЕСТАВРАЦИИ И СОХРАНЕНИЯ ДЕРЕВЯННЫХ КОНСТРУКЦИЙ С ИСПОЛЬЗОВАНИЕМ СОВРЕМЕННЫХ ХИМИЧЕСКИХ ВСПОМОГАТЕЛЬНЫХ ВЕЩЕСТВ - Попков , С.; Попкова, С. (EurasianUnionScientists, 2021)
The object of research is to search for the concrete methods & solutions for cultural heritage objects protection including international experience in this field. It was used and learnt the concrete “case” - conservation VASA vessel in Sweden. It is the only preserved ship dated 17th century. Method. Author has realized the range of investigations targeted for choosing the artificial method of wood aging and experiments with wood samples (pine, spruce) followed by the application of a chemical additive (glyoxal) – one of the most perspective material for wood preservation. Results. Finally, conclusions on the possibilities of applying the results obtained for the needs of unique wooden cultural heritage objects are presented.